Activity Tests Of Sunscreen Emulgel Preparation of Tamanu Oil (Calophyllum inophyllum L.) Combined With Titanium Dioxide (TiO2) - Ni Wayan Devy Indah Lestari; Reslely Harjanti; Dewi Ekowati (Indonesian Journal of Pharmaceutical Education, 2023)
Sunlight is the main source of UV rays, exposure to UV rays can have a negative impact on human skin. These negative impacts can be prevented by using sunscreen. The effectiveness of sunscreen can be increased by combining UV filters and natural ingredients. This study aims to determine variations in the concentration of tamanu oil (Calophyllum inophyllum L.) in an emulgel preparation of a combination of tamanu oil and TiO2 which can provide protection as a Sun Protection Factor (SPF) with good physical quality and stability.Tamanu oil is made in 3 concentration variations of 10%; 15%; and 20% and combined with 7% titanium dioxide. Emulgel preparations as a whole were tested for physical quality and stability tests were carried out using the cycling test method. Testing of sunscreen activity in preparations was carried out in vitro using a UV-Vis spectrophotometer at a wavelength of 290-320 nm. The research results were processed statistically.The results of the sunscreen activity test for the emulgel preparation, a combination of tamanu oil and TiO2, showed that all formulas had activity as a sunscreen. The highest SPF value of the emulgel combination of tamanu oil and TiO2 was in formula 6 (20% oil and TiO2) of 9.6 and after the stability test the SPF formula 6 (20% oil and TiO2) was 9.0.